Delaminated zeolite, ITQ-6 as heterogeneous catalyst for friedel crafts alkylation - Ramli, Zainab; Mohd. Yusoff, Noor Aishikin; Hamdan, Halimaton (The Malaysian Analytical Sciences Society (ANALIS), 2007)

(untitled)
The ability of ITQ-6, a kind of mesoporous zeolitic material to replace microporous zeolite as catalyst has attracted particular attention. In this study, modification of a precursor of microporous ferrierite, PREFER to mesoporous material, ITQ-6 was carried out by delamination technique. The XRD results show that the crystalline phase of PREFER diminished for the sample after delamination. Porosity study of the ITQ-6 sample shows formation of homogeneous mesopores in the size between 3.5-4.0 nm. The acidity study indicates that ITQ-6 still contains appreciable amounts of BrÃ¶nsted and Lewis acidities. Catalytic evaluation of the resulting material, ITQ-6 was carried out in the alkylation of resorcinol with methyl tert-butyl ether which gave 4-tert-butyl resorcinol and 4,6-di-tert-butyl resorcinol as main products. The conversion of resorcinol when using ITQ-6 was ten times higher than ferrierite, FER with similar selectivity of disubstituted product. It shows that the mesoporosity of ITQ-6 was responsible for the higher activity of the catalyst in the reaction.